DAMPAK MEDIA SOSIAL TERHADAP PROSES SOSIALISASI ANAK-ANAK DI SEKOLAH SDN 03 KANDIS - Wulandari, Cherrysa Ariesty; Indarissyifa, Lisa Puspita; Hilmi, Muhammad Akbar (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
The main problem in this study is the intensity of the use of communication media by children is considered to have a very strong influence on the formation of children's character and behavior. The type of research conducted is qualitative research. Data collection techniques are observation, interview, and documentation. The technique used in selecting and determining research subjects is the Snowball Sampling Technique. The results of research with the object of research on children's social behavior and communication media in Makassar city, can be concluded that communication media has become something that is needed by society, from the upper class to the lower class. Communication media is no longer a difficult thing to obtain. Communication media has also spread to all circles and ages as evidenced by the widespread use of communication media in the community, even teenagers and children. It is undeniable that children and adolescents are most vulnerable to being trapped in the bad influence of the media. The use of communication media does not only have a positive impact, but also has a negative impact that can harm its users, especially in children who are quickly influenced and have high curiosity.